Alcohol as Criminogenic Factor - Dimitrijević Vavan, Jelena; Stevković, Ljiljana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
The paper contains a systematic review of recent literature concerning the relationship between alcohol consumption and the development of addiction on one hand, and various types of criminal behaviour and social deviation on the other hand. Different theoretical views and understandings of the nature of the alcohol-crime link are presented at the beginning. Several approaches and models that show whether, to what extent and how alcohol consumption contributes to the perpetration of certain criminal behaviours, misdemeanours, or any deviations are more detailed presented. In considering the research data on alcohol and alcoholism as a criminogenic factor, special attention is dedicated to their impact on the emergence and development of violent crime. Studies which had this link for the subject of research have shown that the connection exists, and that the percentage of violent incidents involving alcohol consumption by the perpetrator is very high. Criminogenic influence of alcohol is especially present in some types of crime, like domestic violence, sexual violence, traffic and juvenile delinquency. Based on the review of relevant literature, it can be concluded that the connection between alcohol/alcoholism and crime is very complex, and that this criminogenic factor should be paid much more attention in the aetiology of crime and social deviation, especially in local criminological research.